Religiosity Reflected In A. Fuadi's The Land Of Five TowersNovel (2011): A Humanistic Psychological Approach - Kurohmah, Uun Mita, Dr. Phil. Dewi Candraningrum, M.Ed (2016)
The major problem of this study is religiosity. The objective of this study is to analyze this novel based on the humanistic Psychological Approach. The Writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source of the study is The Land of Five towers novel by A. Fuadi. Secondary data are the supporting data taken from literary books, criticism, and some articles related to the novel. The secondary data of the study are taken from any information related to the novel. The method of data collection is the reseacher will employ the descriptive qualitative research. Based on the analysis, the reseacher gets some conclusions. The study shows that the problem faced by the major character is his religiosity. It is proven by this dream that becomes the better life. Alif wants to be a successful person for his life.